Pengaruh Ukuran Perusahaan, Profitabilitas, Kepemilikan Saham oleh Publik, dan Leverage Terhadap Pengungkapan Internet Financial Reporting - Insani, Anggia De Silva; Gustati, Gustati; Ihsan, Hidayatul (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of company size, profitability, public ownership, and leverage on Internet Financial Reporting (IFR) disclosures in food & beverage subsector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022. The independent variables in the research are company size, profitability, public ownership, and leverage, while the dependent variable is IFR. The research sample was taken using a purposive sampling method, and 30 companies were obtained that met the sample criteria, resulting in a total of 90 observation data. The analysis technique used is multiple linear regression analysis processed with the SPSS v.25 application. The results of this research show that simultaneously the variables company size, profitability, public ownership and leverage have a positive effect on IFR disclosure, and partially the variables company size and profitability have a positive effect on IFR disclosure. However, the variables of public ownership and leverage have no effect on IFR disclosure.